Exploring student engagegment practises at a South African university: Student engagement as reliable predictor of academic performance - Schreiber, B.; Yu, D. (South African Journal of Higher Education, 2016)
Student engagement is one avenue to explore how the experiences within and beyond the classroom impact student persistence behaviours. This article contributes to the sparse research in South Africa on the correlates of student engagement with academic performance at a Historically Disadvantaged University. The results suggest that engagement practices at this university are different across race and gender and that given the South African history we are able to generalise onto the South African higher education systems. Influences on persistence are complex and require a comprehensive approach which embraces the entire context into which student persistence behaviours are embedded. Engagement and academic performance trends across race and gender suggest that the ideals of the higher education framework of social justice, equity of opportunity and participatory parity remain elusive.